Increasing data completeness in synchrotron tts-microdiffraction experiments for δ-recycling phasing of low-symmetry compounds - Rius, Jordi (2017)
Successful phasing of synchrotron through-the-substrate microdiffraction data by δ-recycling direct-methods largely depends on the number of missing intensities caused by the limited sample rotation range [J. Rius, Direct phasing from Patterson syntheses by δ recycling. Acta Cryst. A 2012, 68, 77–81]. Particularly, for the unfavorable triclinic system, dataset completeness resulting from a single series of consecutive ϕ-scans covering a total ϕ interval of ±35° is around 41%. This value is not enough for the routinary solution of a crystal structure by δ-recycling but can be increased by ~29% by applying the orthogonal χ strategy consisting of merging the information of two series of orthogonal ϕ-scans collected at the same microvolume of the polished thin section. Test calculations using simulated and experimental tts-data of the triclinic mineral axinite confirm that, with the help of the orthogonal χ strategy, crystal structures can be solved routinely. Since data in the ±35 ϕ-interval are normally accessible even for relatively thick glass-substrates (1–1.5 mm), a crystal structure can be determined from a single microvolume. For high-symmetry phases, due to the Laue symmetry redundancy, a single series of ϕ-scans normally suffices for the application of δ-recycling. However, when for experimental causes this series is incomplete, the orthogonal χ strategy also provides a simple way to increase the completeness which besides allowing solving the structure, is also beneficial for the subsequent refinement.